(untitled) (Applied Biological Research, 2022)
A bacterial strain was isolated from a soil near the bank Tapi river, Surat (India) and identified as Streptomyces atacamensis AK3 on the basis of 16s rRNA gene sequencing. The strain possessed reducing agents which enabled it to produce silver nano-particles (AgNPs). The peak observed at 420 nm and turning the broth culture colour to brown indicated the synthesis of AgNPs. Zeta potential of -14 mV revealed a low degree of aggregation of AgNPs. Mostly, AgNPs were spherical, ovoid, and rhomboid. TEM analysis revealed that AgNPs of size 20 nm were most ample. The zones of inhibition (ZOI) against Staphylococcus aureus, Bacillus cereusEscherichia coli and Pseudomonas ± 2, 17 ± 1, 24 ± 2, and 22 ± 2 mm, respectively. The antibiotics or AgNPs: GM30 and MET30 only produced bigger ZOI against S. aureus than 35 μg mL-1 AgNPs. It was only CFS30 that made bigger ZOI against E. coli than 10 μg mL-1 AgNPs. The use of 35 μg mL-1 AgNPs against B. cereus did not yield the similar output as they barely made 17 ± 1 mm ZOI while the use of 35 AgNPs μg mL-1 yielded fruitful results against P. aeruginosa in comparison to those of antibiotics.